2008
DOI: 10.3168/jds.2007-0978
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Nutrient Content in Dairy Manure Using Artificial Neural Network Modeling

Abstract: Nutrients in animal manure are valuable inputs in agronomic crop production. Timely and reliable information on animal manure nutrient content will facilitate the utilization of manure as organic fertilizer and reduce any associated potential environmental problems. The objective of this study was to investigate the feasibility of using multiple linear regression (MLR), polynomial regression, and artificial neural network (ANN) models to determine nutrient content in dairy manure. Fresh manure samples (n = 86)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Livestock manure is complex material and affected by many factors (Westerman et al, 2006), and therefore more complex relationships between manure nutrient and physicochemical properties deserve further investigation. As an example, those with higher accuracy of prediction using artificial neural networks reported by Chen et al (2008). In addition, according to the suggestions by Moral et al (2008), there are few studies on physicochemical models for salinity and heavy metals in comparison with fruitful studies on nutrient content in animal manure.…”
Section: Comparison and Analysis Of The Equations Studiedmentioning
confidence: 86%
“…Livestock manure is complex material and affected by many factors (Westerman et al, 2006), and therefore more complex relationships between manure nutrient and physicochemical properties deserve further investigation. As an example, those with higher accuracy of prediction using artificial neural networks reported by Chen et al (2008). In addition, according to the suggestions by Moral et al (2008), there are few studies on physicochemical models for salinity and heavy metals in comparison with fruitful studies on nutrient content in animal manure.…”
Section: Comparison and Analysis Of The Equations Studiedmentioning
confidence: 86%
“…The proposed correlation laws are linear in the majority of studies, but other reported relationships are polynomial and multi-parametric (Parera i Pous et al, 2010b;Suresh and Choi, 2011;Yagüe et al, 2012). One publication proposes the use of artificial neural network models to determine the nutrient content of dairy cattle manure (Chen et al, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…Nennich et al (2005) showed a linear relationship between crude protein intake and N excretion, which support the argument. Chen et al (2008) also used N feed content to predict manure N content using artificial neural network approach, beside the psychochemical properties of the manure, and the findings demonstrated that the predictors (N feed content and psychochemical properties) and the model were appropriate to predict dairy manure N content. Regarding the partitioning of productive N or manure N to total N, treatment of P. purpureum without supplementation (R1) was the most productive with value of 53%.…”
Section: Manure Excretionmentioning
confidence: 99%